Analisis Akuntabilitas Pengelolaan Dana Desa di Kabupaten Sekadau, Provinsi Kalimantan Barat Tahun 2018 - Lusianus Hendro Santoso; Rosyadi Rosyadi (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2022)
This study aims to analyze and determine the differences and the management and use of Village Funds in Developed Villages, Developing Villages and under-developed Villages in Sekadau Regency. This research uses a qualitative descriptive approach, with documentation analysis and direct interviews. The results showed that the management of Village Funds in Developed Villages, Developing Villages and Under-Developed Villages in Sekadau Regency tended to have the same system and were in accordance with applicable regulations. The use of Village Funds in developed villages has a higher capacity as indicated by the amount of expenditure disbursed by the developed village government, which focuses more on the capital expenditure component than personnel expenditure and expenditure on goods and services. Meanwhile, in developing and underdeveloped villages, the use of village funds in the components of personnel expenditure and goods and services expenditure is almost the same as capital expenditure.